An evaluation of the preschool health check program - O'Regan-Hogan, Moira, 1962- (1995)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1995. Education Bibliography: leaves 121-127 A primary consideration in health care today is the escalating cost of health services and the recognition that there is need to identify ways of delivering quality care at a lower cost. As competition for scarce service dollars grows, the benefits of conducting an evaluation of a program's effectiveness are becoming increasingly apparent. -- This study involved an evaluation of the Preschool Health Check Program in the St. John's and District Health Unit utilizing a descriptive methodology and focusing on program design and process to determine relevance, currency and comprehensiveness. Five separate questionnaires were developed to elicit information concerning the design and process of the program from a variety of groups including Public Health Nurses, Referring Agencies, School Personnel, Key Informants and Parents of Preschool Children. Preschool health screening practices in other provinces were assessed through administration of a questionnaire to Representatives of Provincial and Territorial Departments of Health. A computerized literature search was conducted relative to preschool screening and the specific screening components of vision, hearing, behavior/emotion, speech/language and development contained in the Preschool Health Check Program. Program and followup data were analyzed together with clinic attendance statistics. -- To contribute to the utility of the evaluation and to ensure that data analysis regarding the interpreting and summarizing of results was not conducted in isolation, focus group interviews were held with appropriate public health nursing personnel within the St. John's and District Health Unit. As well, telephone contact was made with the Directors of Nursing of the other Health Units in the province to discuss the current status of the Preschool Health Check Program in their area and to identify issues pertaining to the Program. -- A total of twenty-two recommendations were developed based upon analysis of the findings from these data sources. Of prime consideration was the identification of a need to develop a coordinated and comprehensive public health nursing assessment program for infant and preschool children at risk which would target those children identified at risk during the infant and early preschool period. -- It is anticipated that the recommendations resulting from this Study will assist program managers in decision making related to future resource allocation in the area of child health programming.